2010
DOI: 10.1159/000318019
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative, Postoperative and One-Year Follow-Up of N-Terminal Pro-B-Type Natriuretic Peptide Levels in Volume Overload of Aortic Regurgitation: Comparison with Pressure Overload of Aortic Stenosis

Abstract: Objectives: Limited data are available regarding the impact of pressure or volume overload on the clinical or echocardiographic parameters and the levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in patients with chronic severe aortic valve diseases. We aimed to investigate and compare the relationships between these parameters in such patients. Methods: One hundred twenty-four consecutive patients who underwent aortic valve replacement for chronic severe aortic valve diseases were enrolled. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
4
12
0
Order By: Relevance
“…As shown in Table 2, natriuretic peptides may be useful to detect this maladaptive transition because elevated levels are associated with increased LV and left atrial dimensions, decreased LV function, and increased systolic pulmonary artery pressure. 2,13,16,21,27,29 Figure 4B demonstrates that in most studies, there is an inverse correlation between higher levels of natriuretic peptides and ejection fraction in patients with AS. 2,9,13,15,16,21,22,27,34 One large prospective study of 289 patients referred for TAVR found that higher levels of BNP were independently associated with lower ejection fraction (35.5% versus 55.4%).…”
Section: Bnp and LV Function In Asmentioning
confidence: 89%
See 4 more Smart Citations
“…As shown in Table 2, natriuretic peptides may be useful to detect this maladaptive transition because elevated levels are associated with increased LV and left atrial dimensions, decreased LV function, and increased systolic pulmonary artery pressure. 2,13,16,21,27,29 Figure 4B demonstrates that in most studies, there is an inverse correlation between higher levels of natriuretic peptides and ejection fraction in patients with AS. 2,9,13,15,16,21,22,27,34 One large prospective study of 289 patients referred for TAVR found that higher levels of BNP were independently associated with lower ejection fraction (35.5% versus 55.4%).…”
Section: Bnp and LV Function In Asmentioning
confidence: 89%
“…2,13,16,21,27,29 Figure 4B demonstrates that in most studies, there is an inverse correlation between higher levels of natriuretic peptides and ejection fraction in patients with AS. 2,9,13,15,16,21,22,27,34 One large prospective study of 289 patients referred for TAVR found that higher levels of BNP were independently associated with lower ejection fraction (35.5% versus 55.4%). 24 Iwahashi et al 15 and several other studies confirmed this association.…”
Section: Bnp and LV Function In Asmentioning
confidence: 89%
See 3 more Smart Citations